Antibacterial effect of 3-p-trans-coumaroyl-2-hydroxyquinic acid, a phenolic compound from needles of Cedrus deodara, on cellular functions of Staphylococcus aureus. Issue 9 (29th January 2018) - Wu, Yanping; Bai, Jinrong; Liu, Xiaoyan; Liu, Lijin; Zhong, Kai; Huang, Yina; Gao, Hong
Abstract : Structure–activity relationship of 3- p-trans -coumaroyl-2-hydroxyquinic acid, a phenolic compound from needles of Cedrus deodara, against Staphylococcus aureus and its effect on the cellular functions. Abstract : A natural phenolic compound, 3- p-trans -coumaroyl-2-hydroxyquinic acid (CHQA) from needles of Cedrus deodara, has been reported to exhibit strong antibacterial activity. In this study, the molecular structural requirements of CHQA for the antibacterial activity and its effect on the cellular functions of Staphylococcus aureus were investigated. The structure–activity relationship analysis revealed that the p -coumaric acid moiety of CHQA was critical for the antibacterial activity, while the esterification between p -coumaric acid and 2-hydroxyquinic acid was unfavorable. Studies of the cellular metabolism demonstrated that CHQA induced a significant decrease in the intracellular ATP concentration but no proportional increase in the extracellular ATP. It was also found that CHQA slightly increased the respiratory activity and succinate dehydrogenase activity of S. aureus . Meanwhile, CHQA decreased the DNA synthesis of S. aureus and directly interacted with DNA through the groove binding mode.